Exploring the Untapped Potential: Picrorhiza kurroa Royle Ex. Benth (Kutki) Cultivation in the Western Himalayas- A Review - Rastogi, S.; Kapta, S. K.; Chauhan, Rajesh (Indian Forester, 2025)
Picrorhiza kurroa (Kutki) is an endangered species with a restricted habitat of alpine and sub-alpine vegetation in the Himalayas. It is one of the most sorts after medicinal plant at world level and figured among the 37 identified top priority species for conservation and cultivation in Western Himalayas owing to its narrow distribution range, small population size and high value. Its status in the wild is at risk due to indiscriminate, uncontrolled harvesting and a lack of organized cultivation. The cultivation of Kutki can be a profitable venture for farmers and entrepreneurs due to its increasing demand in the herbal medicine industry. Governments of Himachal Pradesh and Uttarakhand are promoting the cultivation of this plant for the last few years. However the cultivation attempts made by these governments are not sufficient. So more area should be brought under its cultivation to increase the income of the farmers as well as to save the species from extinction. The efforts put by agencies like JICA should be appreciated and there is urgent need that some more organizations should come up to fund projects like this for ensuring the sustainability of the crop.